Personalised medicine : lessons from neurodegeneration to cancer - El-Khamisy, Sherif (Advances in experimental medicine and biology, 2017)
"The mammalian genome is constantly challenged by exogenous and endogenous threats. Although much is known about the mechanisms that maintain genome integrity, little is known about the applications of this knowledge to combat human disease. The past 20 years has witnessed extensive research and progress in this area and scientists started to design new therapies harnessing individual genetic differences among patients to combatdegenerative disorders and cancer. We summarize these advancements and discuss perspectives for the future of personalized medicine"--Publisher's description.